Review of the Neotropical scale insects formerly assigned to Coelostomidiidae and here transferred to a new tribe within the Monophlebidae (Hemiptera: Sternorrhyncha: Coccoidea) - Foldi, I.; Gullan, P. J. (Zootaxa, 2014)
This study reviews the status of all Neotropical genera and species of Coelostomidiidae (Hemiptera: Coccoidea) and transfers them to the family Monophlebidae in the Cryptokermesini Foldi & Gullan tribe n. (the tribe Cryptokermini Tao & Hao is recognised here as a nomen nudum). This change of family placement for Neotropical taxa is based on the morphology of adult males, as supported by the phylogenetic study of Hodgson & Hardy (2013), and by unpublished DNA data. New diagnoses are provided for each of the four recognised genera of Cryptokermesini: Cryptokermes Hempel, Mimosicerya Cockerell, Neocoelostoma Hempel and Paracoelostoma Morrison. The genus Nautococcus Vayssière is considered here to be a junior synonym (syn. n.) of Mimosicerya and the type species of Nautococcus, N. schraderae Vayssière, thus becomes M. schraderae (Vayssière) comb. n. Cryptokermes mexicanus Morrison is transferred to Mimosicerya as M. mexicana (Morrison) comb. n. Also Cryptokermes mimosae Foldi does not fit the morphological concept of Cryptokermes and is excluded from this genus and revision, and from the new tribe; its taxonomic position is uncertain and requires further study. All type species of the Cryptokermesini, including N. schraderae (as M. schraderae), are redescribed and illustrated based on most female instars and available adult males, examined using optical and scanning electron microscopes. Adult males are described and illustrated only for M. schraderae and N. xerophila. Keys are provided to distinguish the Neotropical monophlebid tribes Cryptokermesini and Llaveiini and to recognise each cryptokermesine genus based on female instars and first-instar nymphs. The included species of Cryptokermesini and their known distributions are: Cryptokermes brasiliensis Hempel from Brazil and C. oaxaensis Foldi from Mexico; Mimosicerya hempeli (Cockerell) from Brazil, M. mexicana from Mexico, M. schraderae from Panama and M. williamsi Foldi from Venezuela; Neocoelostoma xerophila Hempel from Argentina, Bolivia, Brazil, Paraguay and Uruguay; and Paracoelostoma peruvianum Morrison from Peru. All these insects live exposed on their host plant, either inside a secreted test (as for female and immature male instars of Cryptokermes, Neocoelostoma and Paracoelostoma) or the strongly sclerotised derm of the preadult female protects the adult (as for all species of Mimosicerya). Adult females of Mimosicerya are pupillarial, remaining within the exuviae of the previous instar, whereas adult females of the other three genera either remain within their test (and some species may be pupillarial) or escape the test to oviposit. The morphology of the adult female and often the preadult female is strongly modified, with reduction of antennae and legs, and with legs lacking in some species.